ANALISIS KESULITAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI KEMAMPUAN METAKOGNISI SISWA - Bibiana Mariina Kapitan Belen; Maria Trisna Sero Wondo; Natalia Peni (Program Studi Pendidikan Matematika, 2023)
This study aims to determine the difficulty of students in understanding mathematical concepts in terms of students' metacognition ability. Students' metacognition ability consists of three categories, namely high, medium and low. The type of research used is qualitative with a descriptive approach. The subjects in this study were 6 students of class VIII of SMPN Satap Watanhura. The selection of subjects is carried out by purposive sampling. Data collection is carried out through questionnaires and test questions on cubes and blocks. The results showed: (1) Students with high metacognition ability did not have any difficulties because they met all indicators completely. (2) Students with metacognition skills are experiencing a little difficulty because they only meet two indicators, namely applying concepts or algorithms to problem-solving, and developing necessary conditions and sufficient conditions of a concept. (3) Students with low metacognition ability experience the most difficult because they do not meet all the indicators of understanding mathematical concepts.